Implementation of The Internet as a Learning Resource For Students - Dwi Putri Lestari; Evi Yuliani; Aulia Utari; Rahmansyah Fadlul Al Karim Rambe (Pena Cendekia Insani, 2024)
This study aims to find out how much the benefits of using the internet as a learning resource for students and teachers are. This research is a research conducted with a literature study using a descriptive method. The data source for this study was taken from journals related to the use of the internet as a learning resource. The technique used is to collect data using listening and note-taking techniques. Data validation -technique uses data triangulation. Data analysis shows that the internet has benefits as a learning resource that can be applied in learning or in teaching and learning activities. Forms of using the internet as a source of learning include supporting learning activities, the internet as a source of information. The results of the study show that everyone knows and uses the internet.